A high gain reduced side‐lobe miniaturized frequency and pattern reconfigurable planar array operating in higher‐order mode. Issue 11 (26th August 2022) - Pal, Joydeep; Gupta, Bhaskar
Abstract: In this work a low profile (˂0.01λ0), single layered, high gain reduced side‐lobe miniaturized microstrip planar array operating at higher‐order broadside mode (HOM) with frequency tuning and 2‐D beam scanning ability is proposed. The gain is enhanced significantly by array configuration using elements operating at TM03 mode. A rectangular slot is etched in the middle of the patch to reduce the side‐lobe level (SLL) below −15 dB in both principal planes. λ /2 parabolic shaped current linkages are connected between the outer λ /2 patch strips supporting TM03 mode to reduce the non‐resonant length from 1.5 λ to 1.167 λ ; hence minimizes the patch area by 22%. A 2 × 2 miniaturized planar array is designed at 2.45GHz using these elements; hence reducing the array footprint. Frequency tuning mechanism is incorporated by placing varactor diodes on the radiating edges of the array elements. Also 360° beam switching at azimuth plane and ± 40° (including 3 dB beam width) at elevation plane is achieved by suitably detuning the varactor capacitances. The simulated and measured results are found to be consistent throughout the 10% frequency tuning range. Maximum 17.1 dBi realized gain is measured which remains consistent within 2 dBi variation for entire frequency tuning and beam scanning range.